2016
DOI: 10.1007/s00280-016-3140-5
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy with 131I-rituximab as consolidation therapy for patients with diffuse large B-cell lymphoma

Abstract: (131)I-rituximab showed promising efficacy as consolidation treatment for patients with DLBCL. A future randomized phase III study to confirm our results is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, no study has been conducted in case of RIT. We demonstrated that effect of lanatoside C as a radiosensitizer at 131 I-trastuzumab RIT in HER2 positive cells ( We have performed the clinical trial of RIT for NHL patients using 131 I-rituximab for 16 years [21][22][23][24][25] . RIT demonstrated excellent outcomes, but there are some refractory patients who revealed resistance to RIT.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has been conducted in case of RIT. We demonstrated that effect of lanatoside C as a radiosensitizer at 131 I-trastuzumab RIT in HER2 positive cells ( We have performed the clinical trial of RIT for NHL patients using 131 I-rituximab for 16 years [21][22][23][24][25] . RIT demonstrated excellent outcomes, but there are some refractory patients who revealed resistance to RIT.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed the clinical trial of RIT for NHL patients using 131 I-rituximab for 17 years 22 26 . RIT demonstrated excellent outcomes, but there are some refractory patients who revealed resistance to RIT.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed a clinical trial of RIT for NHL patients using 131 I-rituximab for 16 years [8][9][10][11][12]. RIT demonstrated excellent results, but some refractory patients showed resistance to RIT.…”
Section: Discussionmentioning
confidence: 99%
“…Among these radiopharmaceuticals, 131 Irituximab plays a role in treating patients with aggressive CD20-expressing B-cell NHL [4][5][6][7]. Our institute has used RIT for NHL patients using 131 I-rituximab [8][9][10][11][12]. RIT using 131 I-rituximab showed remarkable treatment results, but some patients experienced recurrence after RIT, which reveals 3 resistance to the treatment.…”
Section: Introductionmentioning
confidence: 99%